The Russian Professional Sociological Society Needs More Independent Experts - ЗадоринИгорь Вениаминович; ЯковлевАндрей Александрович (Journal of Economic Sociology, 2013)
At the end of 2012 and early 2013, the Higher School of Economics and the Association of Russian Economic Think Tanks (ARETT) conducted a project devoted to modern conditions and trends in the development of think-tanks as a significant segment of independent research in Russia and their roles in the formation of economic policy. An interview with the President of the New Economic Association, Victor Polterovich, carried out within the framework of this project, can be found in the previous volume of Economic Sociology (2013. Vol. 14. No. 3). In-depth interviews with the heads of economic think-tanks and independent economic experts were enriched by several talks with the heads of centres for sociological research, including a conservation with Igor Zadorin, Director General of ZIRCON Research Group. Economic Sociology’s editorial staff is much obliged to Igor Zadorin and Andrey Yakovlev (as team leader of the HSE-ARETT project) for the opportunity to publish the full text of this interview.